IMPLEMENTASI KEBIJAKAN PENYALURAN TUNJANGAN PROFESI GURU PENDIDIKAN AGAMA ISLAM BERBASIS SISTEM INFORMASI DAN ADMINISTRASI GURU AGAMA (Studi Kasus Pada Seksi Pendidikan Agama Islam Kantor Kementerian Agama Kota Malang Tahun 2019) - Billy Rahmawan; M. Mas'ud Said; Rulam Ahmadi (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2021)
Abstract Like the Ministry of Education and Culture, the Ministry of Religion has also allocated TPG for GPAI since the 2008 budget year. TPG or Teacher Professional Allowances are one of the main agendas of the Ministry of Religion in order to improve GPAI's professionalism to create quality education. To facilitate the distribution of the TPG, an application is needed to make it easier for the admin to validate the TPG disbursement feasibility data. From here the Ministry of Religion of the Republic of Indonesia published an online digital-based application called SIAGA or an acronym for the Information System and Administration of Religious Teachers. The benefits of SIAGA application are to overcome the limitations of space and time. This is where the research begins with a research focus, in the form of: (1) The form of public policy implementation from the aspect of the distribution of the Islamic Religious Education Teacher Professional Allowance based on the SIAGA application; (2) Problems in terms of supporting and inhibiting factors from the implementation of the policy for the distribution of these allowances; (3) and alternative forms of solutions to policy implementation problems.The results of this study include: First, the implementation of the SIAGA application at the Ministry of Religion of Malang City, starting with socialization, training, teacher data collection, data verification, to determining the feasibility of disbursing the Teacher Professional Allowance in each teacher and supervisor of Islamic religious education. Second, supporting factors include (1) Communication (2) Human Resources, in this case the admin of the PAIS Section; and (3) positive commitment from all instruments. While the inhibiting factors are: (1) Weaknesses of the Alert System Application (2) the social environment is not conducive. Third, the alternative solutions offered include (1) providing assistance, (2) the Ministry of Religion of Malang City issues a Disposition. Keywords: Policy Implementation, Teacher Professional Allowances, Information Systems and Administration of Religious Teachers (SIAGA)